La relación de la industria creativa y el desarrollo económico en Colombia (2020)
This document consists of research on the orange economy, as it is called by the current government of Colombia, which is also known as the creative economy. It also contains the aspects to be addressed, which are the government plan to incentivize this economy, its investments, achievements in the two years of mandate and the challenges that will be presented after the pandemic by Covid-19, based on data on the influence of the Orange economy on GDP, from 2014 to 2019, with a projection until 2025 and a percentage of participation, to show the growth of the orange economy in our country, future benefits and how to manage the economy after the pandemic, based on data